Prevalence of lxodid Ticks in Cattle Population of Indore, Madhya Pradesh - Mandloi, U.K.; Jayraw, A.K.; Haque, M.; Jamra, N. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
A survey study was conducted to evaluate the prevalence of ixodid ticks in cattle population of Indore, Madhya Pradesh. Every month, ticks were collected from 9511 cattle belonging to randomly selected 5 villages of each tehsil, viz. Indore, Mhow, Depalpur, Sanwer and Hated. The current study revealed an overall tick prevalence of 58.87% with significantly high prevalence of Rhipicephalus (Boophilus) microplus (42.89%) than Hyalomma anatolicum anatolicum (11.82%) and mixed infestation (4.16%). Season-wise, significantly high prevalence was recorded in monsoon (71.08%) than summer (62.28%) and winter (52.12%). Amongst the various age groups, significantly high tick infestation was encountered in 1-3 year-old (78.63%) than >3 year-old (56.79%) and <1 year-old cattle (52.92%). Sex-wise, significantly high tick infestation was documented in males (66.01 %) than their female (58.06%) counterparts. Tehsil-wise, significantly high prevalence was evident in Mhow tehsil (69.12%) as compared to Indore (61.40%), Depalpur (57.27%), Sanwer (55.28%) and Hated (50.14%) tehsils.